If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-21x + 26) = 49(-46 + 9x) Reorder the terms: 8(26 + -21x) = 49(-46 + 9x) (26 * 8 + -21x * 8) = 49(-46 + 9x) (208 + -168x) = 49(-46 + 9x) 208 + -168x = (-46 * 49 + 9x * 49) 208 + -168x = (-2254 + 441x) Solving 208 + -168x = -2254 + 441x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-441x' to each side of the equation. 208 + -168x + -441x = -2254 + 441x + -441x Combine like terms: -168x + -441x = -609x 208 + -609x = -2254 + 441x + -441x Combine like terms: 441x + -441x = 0 208 + -609x = -2254 + 0 208 + -609x = -2254 Add '-208' to each side of the equation. 208 + -208 + -609x = -2254 + -208 Combine like terms: 208 + -208 = 0 0 + -609x = -2254 + -208 -609x = -2254 + -208 Combine like terms: -2254 + -208 = -2462 -609x = -2462 Divide each side by '-609'. x = 4.042692939 Simplifying x = 4.042692939
| 8x-x=-2-3 | | -3(x+4)=5x-10 | | (x+5x)-x=90 | | 0.2(x+1)=3x+7.2 | | -7(3x+1)=-70 | | x^2+n= | | 720x-14000-x^2=0 | | 2x+12=-7x-24 | | n-10=13+15 | | 3(4y+6)-5=1 | | 29+x+x=180 | | -1/2x+3=1 | | 5=-1/2x+3 | | 5-3[7-(3y-6)]= | | 9+7a=8a+5 | | 5(-1)-3=-2-x | | x^4-4x^3-12x^2+24x+5=0 | | 6(2n-1)+6=-3n | | C=35n+500 | | 6=1/36 | | C=2(3.16)r | | 5x-(x-2)=2x+6 | | 72+28+x=180 | | 3v^2+10=7v^2-15 | | x^4-6x^2+8x-5=0 | | 3a-1=95 | | L+w=36 | | f(x)=(x^2+25)(x^3+2x^2-15x) | | -2.3m=-12 | | 2/5=35/n | | 10-z=23 | | -(15/4)-(7) |